Simone Weils frühes Verständnis des Totalitarismus als existenzielle Bedrohung - Arnswald, Ulrich (Labyrinth, 2023)
Coming from anarchist circles and revolutionary-syndicalist trade unions, Simone Weil initially saw herself as a Marxist and an anarchist, before increasingly becoming their early and extremely pointed critic. From 1933 on, she distanced herself more and more from the syndicalist movement in terms of content, and at the same time she was increasingly skeptical of its politics. She saw in the syndicalists, socialists, and communists no more accurate knowledge of society than in the conservatives or fascists. Moreover, she came to realize that they did not have the necessary means of action to carry out a revolution. In the assertion of the "historical mission of the working class," she saw a phrase that served the functionaries but only further humiliated and betrayed the working class. In this respect, even Marxism was for Weil still the intellectual expression of the bourgeoisie, because even a change in property relations would not have eliminated the oppression of the working class. Until the end of her life, she held that instead a radical change in labor relations was necessary to end the oppression of the working class and its social misery. The article attempts to situate Simone Weil's early disillusionment with syndicalism, socialism, Marxism and Stalinism, as well as her recognition of what was widely labelled totalitarianism in Western societies at the latest after the Second World War, in her writings.